Optimisasi Infrastruktur Cloud: Memanfaatkan Keunggulan Serverless dan Blockchain - Nur Adillah, Muhammad Fauzan; Utama, Nur Ichsan (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Cloud infrastructure has become a fundamental foundation in supporting modern applications. Serverless technology and blockchain offer the potential to enhance efficiency, security, and transparency in cloud infrastructure. However, in-depth research on how to optimize cloud infrastructure by leveraging the advantages of these two technologies remains limited. This study aims to explore the potential for optimizing cloud infrastructure by utilizing the benefits of serverless technology and blockchain. The author intends to analyze how the integration of these two technologies can improve the performance, security, and efficiency of cloud infrastructure. A qualitative literature review approach is employed in this research. The author analyzes various literature sources to understand the concepts, benefits, and challenges in optimizing cloud infrastructure by leveraging serverless technology and blockchain. The author's analysis indicates that the integration of serverless and blockchain in cloud infrastructure can enhance system scalability, security, and transparency. However, there are several technical and managerial challenges that need to be addressed to implement this integration effectively.